2018
DOI: 10.1111/aos.13983
|View full text |Cite
|
Sign up to set email alerts
|

Review of rodent hypertensive glaucoma models

Abstract: Glaucoma is a neurodegenerative disease characterized by the progressive loss of retinal ganglion cells (RGCs). Elevated intraocular pressure (IOP) is a primary risk factor for the development and progression of glaucoma. Rodent models of glaucoma have greatly improved our understanding of the pathophysiology of glaucoma and served as a useful tool to investigate neuroprotective agents. An ideal glaucoma animal model should be easy to induce, reproducible, biologically plausible and predictable. Of the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 96 publications
0
50
0
Order By: Relevance
“…The preclinical assessment of drugs aimed at lowering IOP has been traditionally performed on monkeys with artificially increased IOP (Wang et al, 2000), but such experiments are prohibitively expensive and currently rarely conducted due to ethical reasons. Instead, following the development of non-invasive technologies of IOP measurement applicable to small animals, IOP-dependent rodent models have become popular, in which OH is artificially induced (Millar and Pang, 2015;Biswas and Wan, 2019). Although these models reproduce certain aspects of human glaucoma, since retinal ganglion cell (RGC) loss does not develop naturally, an increase in IOP is usually abrupt and may not be long-lasting, and inflammatory components due to physical injury may be a confounding factor.…”
Section: Introductionmentioning
confidence: 99%
“…The preclinical assessment of drugs aimed at lowering IOP has been traditionally performed on monkeys with artificially increased IOP (Wang et al, 2000), but such experiments are prohibitively expensive and currently rarely conducted due to ethical reasons. Instead, following the development of non-invasive technologies of IOP measurement applicable to small animals, IOP-dependent rodent models have become popular, in which OH is artificially induced (Millar and Pang, 2015;Biswas and Wan, 2019). Although these models reproduce certain aspects of human glaucoma, since retinal ganglion cell (RGC) loss does not develop naturally, an increase in IOP is usually abrupt and may not be long-lasting, and inflammatory components due to physical injury may be a confounding factor.…”
Section: Introductionmentioning
confidence: 99%
“…Glaucoma is a multifactorial disease with an elevated IOP as most important risk factor, known until now (19). Several studies showed that an increased IOP leads to RGC loss (20)(21)(22)(23)(24)(25). One molecular mechanism might be seen in the presence of mechanosensitive Piezo channels within the GCL (26).…”
Section: Discussionmentioning
confidence: 99%
“…As an increased IOP induced RGC loss (20)(21)(22)(23)(24)(25), devices, investigating thickness of single RGC layer, might improve the diagnostic value of GCC/GCIPL. SPECTRALIS R offers the possibility of analysis of single GCL layer in a defined macular region with different grids.…”
Section: Discussionmentioning
confidence: 99%
“…Widely used experimental models of glaucoma have been classified as pre-trabecular, trabecular or post-trabecular, using the trabecular meshwork (TM) as an anatomic reference 17 . Multiple limitations have, however, been reported: (1) intracameral injection of viscoelastic substances or microbead particles (pre-trabecular) 18,19 is invasive, with high risk of corneal damage or inflammation, as well as intraocular infections; moreover, some injected substances may reduce the transparency of the optic media, which precludes functional analysis; (2) laser scarring of the TM and/or photocoagulation of the limbal vasculature and episcleral veins (trabecular) 20,21 require expensive equipment, are difficult to apply to pigmented animals due to high and variable absorption of laser energy, and is often accompanied by damage to the TM, corneal inflammation and ulceration, which impair functional assessment 22 ; (3) Morrison’s procedure of injection of hypertonic saline into an episcleral vein (post-trabecular) 23 requires extensive training, and leads to highly variable IOP 7,24 ; (4) Shareef and Sharma’s episcleral vein cauterization (EVC) 25 is also invasive, requires a slow learning curve to access the deep episcleral veins behind the rectus muscles, may lead to venous congestion because the targeted deep venous plexus actually comprises the vortex veins, which drain the entire globe including the choroid 26,27 , and leads to highly variable period of OHT, ranging from 2 weeks to 6–7 months as described by differing authors 25,28,29 .…”
Section: Discussionmentioning
confidence: 99%